THE USE OF STORY FACE STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT AT MA AL-KARIIM BENGKULU TENGAH - Elva Utami; Yuneva Syukur; Vera Anggerayni (English Education Study Program Faculty of Teacher Training and Education, 2020)
The objective of this research was to measure improvement the students in reading comprehension through Story Face Strategy of Narrative text at MA AL-Kariim Bengkulu Tengah. This reserach was conducted using classroom action. In conducting this research, the researcher used of story face strategyto improve students reading comprehension of narrative text. The researcher chose second grade students of MA Al-Kariim Bengkulu Tengah as the sample of the research. Class XI IPS consists of 26 students. Therefore, the subjects of this research were26 students. The finding of this research showed that Story Face strategy improved the students’ reading comprehension at second grade of MA Al-Kariim Bengkulu Tengah. The percentage of students who passed the minimum mastery criterion improved continuallly from baseline data to cycle 1, cycle 2, and cycle 3. The mean score also improved continually from baseline to cycle 3.The researcher suggested the following points: English teachers can apply Face Story strategy as one of the alternative way to improve students’ reading comprehension and to improve students’ academic achievement. It could help the teacher in applying various activities in the classroom. Further research is highly recommended to find as many as good reading strategy and technique to be applied in the classroom. By finding other strategy and technique, it hopes can create better reading comprehension for the students